Optimizing The Application of The Presumption of Innocence In Indonesia's Enforcement Against Terrorist - Indra Miza; Eriyantouw Wahid; Gunawan Djajaputra (International Journal Labs, 2021)
In the law enforcement against perpetrators of criminal acts of terrorism, protection of human rights must be prioritized even though the act constitutes an extraordinary crime which must be condemned regardless of the reasons and motives. The principle of presumption of innocence must also be upheld because the principle of presumption of innocence is a norm or rule that contains provisions that must be implementedby law enforcement officials to treat a suspect or defendant like an innocent person even though the evidence indicates the fault of a suspect or defendant. In the application of the presumption of innocence principle, law enforcers must really be able to implement it even though sometimes in the field implementation there are pro and contra when making decisions to take action against terrorists. Therefore, it is necessary to optimize law enforcement based on the presumption of innocence, both as stated in the Criminal Procedure Code (KUHAP) and the terrorism law so that law enforcement can prioritize the presumption of innocence and can avoid abuse of authority by law enforcement.